Design Answer Agent And Knowledge Repository For IQA (Interactive Question Answering) On Swamedikasi Mild Illness - Agus Mulyanto; Yeni Agus Nurhuda; Tony Reza Apriyanto (Proceeding International Conference on Information Technology and Business, 2017)
Self-medication is a self-administered treatment, Self-medication is the most public effort to overcome the symptoms of disease without medical supervision. Lack of public knowledge about over-the-counter and drug-limited medicines in drug services. Therefore, there is a need for a system to find related information about Self-Medication knowledge, such as a system that can answer questions posed by user interactively about knowledge of Self-medication or commonly known as interactive question and answer system. Self-Medication Interactive Question Answering System (SMIQA) is a question and answer system about minor illnesses that can be tried the medicine. To be able to build SMIQA it is necessary to establish a knowledge repository of an agent’s reply containing the knowledge of Self-Medication of a common health problems compiled using a tree structure stored in an AIML document. While the answer agent is a system that serves to find answers. To find answers in the knowledge repository will be used state concept information. This research produces Answer Agent design for IQA (Interactive Question Answering) on swadication of minor ailments based on free and restricted drug use according to the health department 2007. Testing conducted is a recall test where the data in the test is based on the sentence question, statement, dialogue grouding and clarification, and ellipsis dialogue with the results of the total accuracy of the test recall of 97.58% Keywords: Answer Agent, AIML, Interactive Answering Question, Knowledge Repository, and Self-Medication.